ПОВЫШЕНИЕ ТОЧНОСТИ УЗКОДИАПАЗОННЫХ ИМПЕДАНСОМЕТРИЧЕСКИХ КАНАЛОВ ПРЯМОГО ПРЕОБРАЗОВАНИЯ - Мельник, В.Г.; Семенычева, Л.Н. (Інститут електродинаміки НАН України, Київ, 2011)
The paper deals with the results of researches of precision measurement channel, which is based on the AC bridge circuit with integral digital to analogy converter and an indicator of balance, which includes high-sensitivity integrating- type analogy to digital converter such as MAXI 32. Results of researches of the linearity characteristics of the transformation of the channel are given, its specific error are discussed. The ways of significantly reducing the errors caused by the nonlinearity characteristics of the ADC are proposed. References 12, figures 6.